Unsur Kebudayaan Dalam Seni Pertunjukan Kabuki - Putra Mahardika A.A. Ngurah; Wayan Nurita (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2024)
ABSTRACT A culture is an indispensable part of identity of a country, passed down from time to time for generations. Like other countries in the world, Japan have a diverse culture, one of them is Kabuki (歌舞伎) who have been exist for 400 years as Japan art of theatre. This research purpose to find seven cultural elements in theatre art of Kabuki (歌舞伎) in Japan. The theory used in this research is Koentjaraningrat’s Seven Cultural Elements Theory. The data source used is primary data collected from documentary videos related to this research used to find solutions to existing problems. The technique used to analyze the data is descriptive qualitative research technique. The results showed that in Kabuki (歌舞伎) have seven cultural elements which is religious system, knowledge system, language system, art system, society system, technology system, and livelihood system. Keywords: Culture, Research, Kabuki (歌舞伎)